Оцінка та створення вихідного матеріалу для селекції люцерни посівної в умовах підвищеної кислотності ґрунтів - Бугайов, В.Д.; Мамалига, В.С.; Горенський, В.М.; Максімов, А.М. (Фактори експериментальної еволюції організмів, 2014)
Aims. The estimation and creation of the outgoing material for alfalfa crop selection in enhanceable acidity of soil (pH 5.0–5.5). The estimation of collective and hybrid material was done according common methods. Results. According to results of long-term researches of 394 collective sort standards of alfalfa crop of various ecogeographical origin, the genotypes that are tolerant to the soil acidity with the relatively high feeding and seed productivity are mentioned. With the usage of mentioned in recent years collective sort standards the hybrid material has been created in the amount of 87 populations and the estimation of it has been done. Among then there are 7 hybrid populations (F2) which exceed the average (in 2011–2012) the standard sort Syniukha as to the crop of the dry material 2–8 and seeds 8–58 %. Conclusions. The received results of investigation prove the high estimation as genetic sources tolerant signs to the higher soil acidity of sort standards Zhydrune (Litva), Vika (Denmark), Yaroslavna and Syniukha (Ukraine), Mega (Switzerland) and the perspective outgoing material hybrid populations received with their participation.